Redox-sensitive Pluronic F127-tocopherol micelles: synthesis, characterization, and cytotoxicity evaluation - Liu Y (Dove Medical Press, 2017)
Yuling Liu,1,2,* Sai Fu,1,* Longfei Lin,1 Yuhong Cao,3 Xi Xie,3 Hua Yu,2 Meiwan Chen,2 Hui Li1 1Institute of Chinese Materia Medica, China Academy of Chinese Medical Sciences, Beijing, 2State Key Laboratory of Quality Research in Chinese Medicine, Institute of Chinese Medical Sciences, University of Macau, Macau, People’s Republic of China; 3Department of Materials Science and Engineering, Stanford University, Stanford, CA, USA *These authors contributed equally to the work Abstract: Pluronic F127 (F127), an amphiphilic triblock copolymer, has been shown to have significant potential for drug delivery, as it is able to incorporate hydrophobic drugs and self-assemble into nanosize micelles. However, it suffers from dissociation upon dilution owing to the relatively high critical micelle concentration and lack of stimuli-responsive behavior. Here, we synthesized the α-tocopherol (TOC) modified F127 polymer (F127-SS-TOC) via a redox-sensitive disulfide bond between F127 and TOC, which formed stable micelles at relatively low critical micelle concentration and was sensitive to the intracellular redox environment. The particle size and zeta potential of the F127-SS-TOC micelles were 51.87±6.39 nm and -8.43±2.27 mV, respectively, and little changes in both particle size and zeta potential were observed within 7 days at room temperature. With 10 mM dithiothreitol stimulation, the F127-SS-TOC micelles rapidly dissociated followed by a significant change in size, which demonstrated a high reduction sensitivity of the micelles. In addition, the micelles showed a high hemocompatibility even at a high micelle concentration (1,000 µg/mL). Low cytotoxicity of the F127-SS-TOC micelles at concentrations ranging from 12.5 µg/mL to 200 µg/mL was also found on both Bel 7402 and L02 cells. Overall, our results demonstrated F127-SS-TOC micelles as a stable and safe aqueous formulation with a considerable potential for drug delivery. Keywords: Pluronic F127, tocopherol, reduction sensitivity, micelles, hemolysis